The shadow and photon sphere of the charged black hole in Rastall gravity. (28th July 2021) - Guo, Sen; He, Ke-Jian; Li, Guan-Ru; Li, Guo-Ping
Abstract: Considering a charged black hole (BH) surrounded by a perfect fluid radiation field (PFRF) in Rastall gravity, we investigate this BH shadow and photon sphere on different spherical accretions backgrounds. The effect of the PFRF parameter/BH charge on the critical impact parameter is studied by investigating the light deflection near this BH. The luminosity of these BH shadows in different spherical accretions is obtained, respectively. It is found that the shadow of this BH with infalling spherical accretion is darker than static spherical accretion, and the photon sphere with infalling spherical accretion is brighter than a static one. We creatively investigate the effects of the BH charge/PFRF parameter on the luminosity of BH shadow and photon sphere. The results implying that the BH shadow is a signature of space-time geometry, and the photon sphere luminosity is affected by accretion materials and BH itself.